ChemInform Abstract: Nano‐Composites for Water Remediation: A Review. Issue 43 (21st October 2014) - Tesh, Sarah J.; Scott, Thomas B.
Abstract Review: including a discussion what kind of developments are needed to achieve commercial maturity; 180 refs.